The Prognostic Value of Gastric Immune Prognostic Index in Gastric Cancer Patients Treated With PD-1/PD-L1 Inhibitors - Chen, Li; Zhao, Ruihu; Sun, Hao; Huang, Rong; Pan, Hongming; Zuo, Yanjiao; Zhang, Lele; Xue, Yingwei; Li, Xingrui; Song, Hongjiang (Frontiers in Pharmacology, 2022)
Objective: This study aimed to investigate the prognostic value of gastric immune prognostic index (GIPI) in gastric cancer patients treated with programmed death 1/programmed death-ligand 1 (PD-1/PD-L1) inhibitors. Methods: This study was performed to elucidate the role of GIPI using the data from 146 gastric cancer patients treated with PD-1/PD-L1 inhibitors between August 2016 and December 2020 in Harbin Medical University Cancer Hospital. GIPI was calculated based on dNLR and LDH. Patients were categorized into three groups: (1) GIPI good (LDH≤250 U/L and dNLR≤3); (2) GIPI intermediate (LDH>250 U/L or NLR>3); (3) GIPI poor (LDH>250 U/L and dNLR>3). The correlations between GIPI and clinicopathologic characteristics were determined by the Chi-square test or the Fisher' s exact test. The Kaplan-Meier analysis and log-rank test were used to calculate and compare progression-free survival (PFS) and overall survival (OS). The univariate and multivariate Cox proportional hazards regression model was used to detect prognostic and predictive factors of PFS and OS. Results: 146 patients treated with PD-1/PD-L1 inhibitors were included in this study, of which, 72.6% were with GIPI good, 23.3% were with GIPI intermediate, and 4.1% were with GIPI poor. The GIPI was associated with the common blood parameters, including neutrophils and lymphocytes. The multivariate analysis showed that platelet, TNM stage, treatment were the independent prognostic factors for PFS and OS. Patients with GIPI intermediate/poor were associated with shorter PFS (median: 24.63 months vs. 32.50 months; P=0.078) and OS (median: 28.37 months vs. not reached; P=0.033) than those with GIPI good. GIPI intermediate/poor was correlated with shorter PFS and OS than GIPI good, especially in subgroups of patients with ICI treatment and patients with PD-1/PD-L1 positive status. Conclusions: The GIPI correlated with poor outcomes for PD-1/PD-L1 expression status and may be useful for identifying gastric cancer patients who are unlikely to benefit from treatment.